Chronic Trichuris muris infection alters hematopoiesis and causes IFN‐γ‐expressing T‐cell accumulation in the mouse bone marrow. Issue 11 (26th September 2016) - Chenery, Alistair L.; Antignano, Frann; Hughes, Michael R.; Burrows, Kyle; McNagny, Kelly M.; Zaph, Colby
Abstract : During the peak of chronic intestinal Trichuris muris infection in mice, we show enhanced, IFN‐γ‐driven proliferation/differentiation of hematopoietic stem cells (HSC) and concurrent accumulation of IFN‐γ+ T cells in the bone marrow. These results provide insight into the systemic effects of intestinally‐restricted helminth infections on the bone marrow. Abstract : Proinflammatory cytokines produced during immune responses to infectious stimuli are well‐characterized to have secondary effects on the function of hematopoietic progenitor cells in the BM. However, these effects on the BM are poorly characterized during chronic infection with intestinal helminth parasites. In this study, we use the Trichuris muris model of infection and show that Th1 cell‐associated, but not acute Th2 cell‐associated, responses to chronic T. muris infection cause a major, transient expansion of CD48 − CD150 − multipotent progenitor cells in the BM that is dependent on the presence of adaptive immune cells and IFN‐γ signaling. Chronic T. muris infection also broadly stimulated proliferation of BM progenitor cells including CD48 − CD150 + hematopoietic stem cells. This shift in progenitor activity during chronic T. muris infection correlated with a functional increase in myeloid colony formation in vitro as well as neutrophilia in the BM and peripheral blood. In parallel, we observed an accumulation of CD4 +, CD8 +, and CD4 − CD8 − (double negative) T cells that expressed IFN‐γ, displaying activated and central memory‐type phenotypes in the bone marrow during chronic infection. Thus, these results demonstrate that Th1 cell‐driven responses in the intestine during chronic helminth infection potently influence upstream hematopoietic processes in the BM via IFN‐γ.